Body physical parameters instead of water equivalent diameter to calculate size-specific dose estimate in adult chest CT - Hu, Xiaoyan; Gou, Jie; Yang, Fan; Guo, Dajing (Scientific reports, 2024)
This study aimed to investigate body physical parameters as substitutes for water equivalent diameter (Dw) while calculating size-specific dose estimates (SSDEs) during adult chest computed tomography (CT). A retrospective analysis was conducted on 776 patients. Patients were divided into training set (542 patients) and validation set (234 patients) according to a ratio of 7:3. The correlations between physical parameters and Dw were analyzed. The differences between SSDE substitutes and the reference SSDE (SSDE reference ) were compared. Strong positive correlations were observed between body mass index (BMI) and Dw as well as between weight and Dw in overall, male, and female patients (all p < 0.001). The correlations between BMI and Dw were stronger than those between weight and Dw in overall, male, and female subjects (all p < 0.001). SSDE weight and SSDE BMI were not significantly different from SSDE reference ( p > 0.05). The RMSEs of overall patients between SSDE weight and SSDE reference as well as between SSDE BMI and SSDE reference were 0.237 and 0.2, respectively. The use of sex-specific regression equations for BMI caused a slightly reduction in RMSE. Weight and BMI can be used as surrogate parameters for Dw when calculating SSDE in adult chest CT exams, with BMI being the preferred substitute parameter.